Targeting the DNA damage response: PARP inhibitors and new perspectives in the landscape of cancer treatment. (December 2021) - Genta, Sofia; Martorana, Federica; Stathis, Anastasios; Colombo, Ilaria
Graphical abstract: Highlights: DNA damaging agents have proven significant efficacy in the treatment of different type of malignancies. PARP inhibitors are among the most effective targeted agents, particularly in the setting of BRCA mutations. Combination strategies have been investigated to overcome PARP inhibitors primary or acquired resistance. Cell cycle check point inhibitors represent a new strategy to tackle the DNA damage response. Abstract: Cancer derives from alterations of pathways responsible for cell survival, differentiation and proliferation. Dysfunctions of mechanisms protecting genome integrity can promote oncogenesis but can also be exploited as therapeutic target. Poly-ADP-Ribose-Polymerase (PARP)-inhibitors, the first approved targeted agents able to tackle DNA damage response (DDR), have demonstrated antitumor activity, particularly when homologous recombination impairment is present. Despite the relevant results achieved, a large proportion of patients fail to obtain durable responses. The development of innovative treatments, able to overcome resistance and ensure long-lasting benefit for a wider population is still an unmet need. Moreover, improvement in biomarker assays is necessary to properly identify patients who can benefit from DDR targeting agents. Here we summarize the main DDR pathways, explain the current role of PARP inhibitors in cancer therapy and illustrate new therapeutic strategies targeting the DDR, focusing on the combinations of PARP inhibitors with other agents and on cell-cycle checkpoint inhibitors.